Super austenitic stainless steel with reduced dynamic strain aging characteristics and preparation method thereof
By adding Mo, Cr, Ni and nitrogen elements to 316L stainless steel, a new super austenitic stainless steel was prepared, which solved the problem of dynamic strain aging in high-temperature plastic deformation, and achieved the improvement of high-temperature mechanical properties and the delay of DSA behavior.
Patent Information
- Application Number
- CN202411982631.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Super austenitic stainless steel is prone to dynamic strain aging during plastic deformation at high temperature, resulting in plastic deformation instability of the material during plastic deformation, reducing the surface quality and tensile plasticity of the material.
By adding Mo, Cr, Ni and nitrogen elements to the 316L stainless steel, a new super austenitic stainless steel was prepared. High molybdenum makes the grain refinement of the steel grain and the high temperature strength increase, delaying the occurrence of dynamic strain aging; chromium and nickel elements improve corrosion resistance, and nitrogen elements maintain a co-equality relationship with the matrix, significantly strengthening the austenitic stainless steel.
It effectively suppresses dynamic strain aging behavior, improves high-temperature mechanical properties, delays the temperature range of DSA, and enhances the corrosion resistance and comprehensive performance of the material.
Smart Images

Figure CN119776735A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to a super austenitic stainless steel with reduced dynamic strain aging characteristics and a preparation method thereof. Background Art
[0002] In order to solve the problems of insufficient corrosion resistance and high-temperature strength of ordinary austenitic stainless steel, a series of more corrosion-resistant and higher-strength super austenitic stainless steels have gradually been developed. By increasing the content of alloy elements, the corrosion resistance and mechanical properties of super austenitic stainless steel are continuously improved, and it has broad application prospects in extremely harsh environments such as flue gas desulfurization, petrochemical industry, and seawater desalination.
[0003] The 316Mo super austenitic stainless steel obtained by injection molding technology has the characteristics of high toughness, good corrosion resistance and wear resistance, non-ferromagnetic properties and good biocompatibility. It is widely used in marine engineering, aerospace, petrochemical, biomedicine and other fields, and has become a new generation of resource-saving high-performance green advanced materials. Metal injection molding (MIM) is a new type of metal material near-net forming technology that combines traditional powder metallurgy die-sintering technology with injection molding technology. It has unique advantages in the production of small and complex parts, high mechanical properties, high dimensional accuracy, and mass production. In addition, this technology uses finer powder particle size, which is conducive to diffusing nitrogen into powder particles to increase nitrogen content, and finally obtain high-nitrogen stainless steel, which can shorten the diffusion distance of nitrogen, make the distribution of nitrogen more uniform, and greatly shorten the nitriding time.
[0004] However, the super austenitic stainless steel will experience dynamic strain aging (DSA) during high-temperature plastic deformation, which will cause the material to produce plastic deformation instability during plastic deformation, namely the PLC (Portevin-Le Chatelier) effect. When the alloy material is tensilely deformed, the influence of dynamic strain aging will cause a zigzag flow phenomenon on the tensile curve and the formation and propagation of deformation bands on the surface of the material, which is called the PLC effect. The PLC effect is also known as serrated yielding. This deformation instability phenomenon can easily cause uneven local deformation of the material during high-temperature plastic deformation, forming obvious local deformation bands on the surface of the material, which will not only reduce the surface quality of austenitic stainless steel, but also deteriorate tensile plasticity.
[0005] The microscopic mechanism of the PLC effect is generally believed to be dynamic strain aging (DSA), that is, the interaction between solute atoms and movable dislocations. Since super austenitic stainless steel contains not only interstitial elements such as N and C, but also substitutional elements such as Cr, Nb, and Mo, the Cr precipitated in the alloy 23Second phases such as C6, Cr2N, and NbC will also have a significant impact on the atomic diffusion and dislocation movement of stainless steel.
[0006] In order to reduce the dynamic strain aging caused by the precipitation of the second phase, a 316Mo super austenitic stainless steel is first prepared by adding Mo element to 316L stainless steel. High molybdenum can increase the critical strain of stainless steel for PLC effect, delay the occurrence of dynamic strain aging and change the type of PLC band, thereby effectively inhibiting zigzag flow. Secondly, according to the serration changes of 316Mo austenitic stainless steel due to DSA (when the temperature is close to the critical lower limit of DSA (450℃), the serration type is A-type, with large and sparse serration intervals and large amplitude; at 450℃ high strain, irregular up and down moving E-type sawtooth waves appear; as the temperature rises to 550℃, small and high-frequency A+B-type composite sawtooth appears; finally, at the critical upper limit temperature of DSA (650℃), C-type sawtooth waves appear, which are formed by the moving dislocations breaking free instantly after being pinned by the solid solution atomic gas group), it shows that the addition of nitrogen will not only increase the stacking fault energy of austenite, reduce the interaction between defects and stacking faults, and make DSA occur at higher strains, but also delay the appearance of the critical strain value of high-temperature serrations, change the serration characteristics and weaken the amplitude of high-temperature serrations. Nitrogen solid solution in the matrix causes lattice distortion, interacts with dislocations, and hinders dislocation movement to increase the strength of austenitic steel. At the same time, nitrogen can work together with chromium in an oxidizing environment to form a stable oxide film, thereby improving the corrosion resistance and overall performance of stainless steel.
[0007] The Chinese patent number is CN118756056A "A method for preparing high nitrogen austenitic stainless steel", which reports a method for preparing high nitrogen austenitic stainless steel. The lattice constant of stainless steel is changed mainly by the addition of nitrogen, thereby affecting its mechanical and physical properties. However, the organizational stability of high nitrogen austenitic stainless steel is poor under high temperature conditions, and heating will lead to the precipitation of second phases such as intermetallic compounds, nitrides, carbides, and carbonitrides. When the precipitated phase is sheared by dislocations, zigzag behavior will appear in austenitic stainless steel, triggering the DSA effect. Summary of the invention
[0008] In view of the above shortcomings of the prior art, the first object of the present invention is to provide a super austenitic stainless steel with reduced dynamic strain aging characteristics. The injection molded super austenitic stainless steel provided by the present invention can ensure that the high temperature mechanical properties are improved while suppressing the dynamic strain aging behavior.
[0009] The second object of the present invention is to provide a method for preparing the above-mentioned super austenitic stainless steel with reduced dynamic strain aging characteristics.
[0010] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0011] The invention provides a super austenitic stainless steel with reduced dynamic strain aging characteristics. The super austenitic stainless steel has the following components, measured by mass percentage: 20-23% Cr, 14-16% Ni, 4.4-6.8% Mo, 0.01-0.2%, 0.179-0.296% N, ≤0.10% O, ≤1% Mn, ≤1% Si, and the balance is Fe and unavoidable impurities.
[0012] The super austenitic stainless steel provided by the present invention is based on traditional 316L stainless steel, and has added chromium, nickel, molybdenum and nitrogen elements. Among them, high molybdenum refines the grain and improves the high-temperature strength of the steel, delays the occurrence of dynamic strain aging, and thus inhibits zigzag flow; chromium and nickel elements can not only improve its corrosion resistance, but also work together with nitrogen elements and precipitate in the form of nitrides. The nitrides maintain a coherent relationship with the matrix, thereby significantly strengthening the austenitic stainless steel. The addition of these elements continuously improves its corrosion resistance and high-temperature mechanical properties and can be used in various extremely harsh environments and demanding scenarios.
[0013] In a preferred embodiment, the super austenitic stainless steel has the following composition, by mass percentage: Cr 20-23%, Ni 14-16%, Mo 4.4-6.8%, C 0.01-0.2%, N 0.266-0.296%, O≤0.10%, Mn≤1%, Si≤1%, and the remainder is Fe and unavoidable impurities.
[0014] The present invention also provides a method for preparing super austenitic stainless steel with reduced dynamic strain aging characteristics, comprising mixing super austenitic stainless steel powder with a binder to obtain a feed material, injection molding the feed material to obtain a rough blank, catalytically degreasing the rough blank to obtain a degreased blank, nitriding and sintering the degreased blank to obtain a sintered blank, and heat treating the sintered blank to obtain the super austenitic stainless steel.
[0015] In a preferred embodiment, the super austenitic stainless steel powder is prepared by a gas atomization method, the gas atomization pressure is 2-8 MPa, and the gas atomization medium is nitrogen.
[0016] In the actual operation process, various raw materials are selected according to the composition of super austenitic stainless steel, and the resulting alloy liquid is subjected to gas atomization treatment after smelting.
[0017] In a preferred embodiment, the particle size of the super austenitic stainless steel powder is D 10 =3-12μm, D 50 =9-18μm, D 90 =15-30μm.
[0018] The super austenitic stainless steel powder prepared by the gas atomization method has fine and uniform particle size and narrow distribution.
[0019] In a preferred solution, the mass fraction of N in the super austenitic stainless steel powder is 0.01-0.02%. Due to the combined effect of the atomizing medium nitrogen and the alloying elements at high temperature, a certain amount of nitrogen is dissolved in the powder.
[0020] In a preferred embodiment, the mass fraction of the binder in the feed is 10-11%.
[0021] In a preferred embodiment, the binder is a composite polyoxymethylene-based adhesive.
[0022] In a preferred embodiment, the mixing temperature is 170-180° C., the mixing time is 1.5-2 h, and the mixing speed is 30-35 r / min.
[0023] In a preferred embodiment, during the injection molding, the temperature of the mold is 90-100° C., the maximum injection temperature is 175-185° C., and the injection pressure is 80-90 MPa.
[0024] In a preferred embodiment, the catalytic degreasing is carried out in a fuming nitric acid atmosphere, the temperature of the catalytic degreasing is 110-120° C., and the time of the catalytic degreasing is 4-6 hours.
[0025] In a preferred embodiment, the nitriding sintering temperature is 1290-1340° C., the holding time is 1-4 hours, and the partial pressure of nitrogen is 20 Kpa-80 Kpa.
[0026] Further preferably, the nitriding sintering process is composed of a negative pressure degreasing stage, a vacuum sintering stage, a partial pressure sintering stage, and a forced cooling stage. The process of the negative pressure degreasing stage is: firstly, the temperature is increased to 350-400°C at a heating rate of 3-5°C / min and kept for 30-120min, then the temperature is increased to 600-650°C at a heating rate of 3-5°C / min and kept for 30-240min. During the negative pressure degreasing stage, the gas pressure is controlled to be 0.001-0.1Pa, and the flow rate of the protective gas is 20-30L / min; the process of the vacuum sintering stage is: the temperature is increased to 1000-2000°C at a heating rate of 3-5°C / min. The temperature is kept at 1100°C for 30-90min. During the vacuum firing stage, the gas pressure is controlled to be 0.001-0.1Pa, and no protective gas is introduced. The process of the partial pressure sintering stage is: heating to 1290-1340°C at a heating rate of 3-5°C / min, and keeping for 120-240min. During the partial pressure sintering stage, the partial pressure of the protective gas is controlled to be 20-80KPa, and the flow rate of the protective gas introduced is 20-30L / min. The process of the cooling stage is: cooling to 800-850°C at a cooling rate of 5-15°C / min, and then cooling with the furnace. The protective gas introduced in the partial pressure sintering stage is nitrogen.
[0027] In the present invention, the obtained degreased blank is first placed in a vacuum sintering furnace, firstly further hot degreasing is carried out through a negative pressure degreasing stage, then the residual air after degreasing is further discharged through a vacuum sintering stage, and preliminary sintering is carried out, then, nitrogen is introduced in the partial pressure sintering stage, and the nitrogen partial pressure is controlled to nitridize the super austenitic stainless steel, and finally the cooling stage is carried out at 5-15°C / min to 800-850°C and then cooled with the furnace, so as to avoid the austenitic stainless steel staying in the sensitization zone for too long, chromium carbide will be formed along the grain boundary, resulting in the appearance of a chromium-poor zone at the edge of the grain boundary, thereby reducing the corrosion resistance of the sample, and controlling the cooling rate can affect the precipitation process and morphology of precipitates such as nitrides, thereby optimizing the performance of the austenitic stainless steel.
[0028] Preferably, the heat treatment is a solution treatment, the temperature of the solution treatment is 1100° C.-1150° C., the time of the solution treatment is 2-4 hours, and water cooling is performed after the solution treatment is completed.
[0029] The present invention finally has Cr in the structure after solution treatment. 23 Second phases such as C6 and Cr2N are dispersed in the matrix to form a supersaturated solid solution, which hinders the movement of dislocations and thus improves the strength of the material. The size is 20-30μm and the spacing is 20-50μm. As the nitrogen content increases, the content of blocky matter in the solid solution sample organization is significantly reduced, which increases the fine grain strengthening.
[0030] However, the parameters of the solid solution need to be effectively controlled. If the solid solution treatment is carried out at too high a temperature, the nitrogen-containing second phase precipitation phase will increase sharply, reducing the plasticity and toughness of the stainless steel and affecting its corrosion resistance. If the solid solution treatment is carried out at too low a temperature, the precipitated phase cannot be fully dissolved or redistributed, thus affecting the performance optimization of the material. If the heat treatment is carried out for too long a time, the internal grains of the material may grow and reduce its mechanical properties. If the heat treatment is carried out for too short a time, the internal structure of the material may not be able to complete the required phase change process, resulting in poor heat treatment effect.
[0031] The super austenitic stainless steel provided by the present invention can obtain a tensile strength of 353-670MPa, a yield strength of 180-315MPa and an elongation after fracture of 20-53% when stretched at 350°C-750°C. After the stretching is completed, the surface of the 316Mo+0.179N% stainless steel has a slight roughness phenomenon at the breaking point, the surface of the 316Mo+0.266N% and 316Mo+0.296N% stainless steel samples is smooth after breaking without roughness, and the surface of the 316Mo+0N% stainless steel sample prepared by introducing argon as a protective atmosphere in the partial pressure sintering stage has obvious surface roughness.
[0032] The super austenitic stainless steel provided by the present invention has no dynamic strain aging below 400°C, and at 450°C, the stress-strain curve shows an E-type sawtooth wave that moves up and down irregularly at the initial stage of strain, and at 550°C, the stress-strain curve shows a small amplitude and fine high-frequency A+B-type composite sawtooth, and the critical strain shows a gradually increasing trend with the increase of nitrogen content, and the strain value increases from 2.545% to 3.919%. At the same time, the end temperature of DSA also increases accordingly. Compared with 316Mo+0N%, 316Mo+2.296N% still shows a severe sawtooth effect on the stress-strain curve at 750°C.
[0033] After high-temperature stretching, the super austenitic stainless steel provided by the present invention has a larger dimple and more spherical precipitates at the fracture as the nitrogen content increases. With the occurrence of DSA, the Mo precipitate phase of the non-nitrided 316Mo+0N% stainless steel is basically integrated into the matrix, and a large number of blocky grain boundaries disappear on the fracture surface. The DSA of the 316Mo+0N% stainless steel is related to the replacement of atoms Cr and Mo. In the super austenitic stainless steel provided by the present invention, with the addition of nitrogen content, the diffusion rate of Cr and Ni in the alloy of the 316Mo+0.266N% stainless steel at 650°C is increased, and the interaction with interstitial atoms such as C and N and the second phase is more intense, forming a new dislocation pinning relationship, which promotes Cr 23 The nitrogen-containing second phases such as (C, N)6 and Cr2N precipitate, the precipitates increase at the fracture, the critical strain value increases, and the dynamic strain aging (DSA) behavior is delayed.
[0034] The present invention focuses on the influence of nitrogen content on the dynamic strain effect of 022Cr21Ni15MoN (316Mo) super austenitic stainless steel in high temperature processes. By obtaining 316Mo samples with different nitrogen contents under different nitrogen partial pressures, the samples are subjected to medium and high temperature uniaxial tensile tests to analyze the influence of nitrogen content on the dynamic strain aging of 022Cr21Ni15MoN (316Mo) super austenitic stainless steel.
[0035] While significantly suppressing dynamic strain aging, the purpose of improving medium and high temperature performance is achieved, thereby expanding the application scope of the alloy and having important application value in industry.
[0036] Beneficial Effects
[0037] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:
[0038] 1. The present invention reduces the dynamic strain aging characteristics of 316Mo injection-molded super austenitic stainless steel at high temperature by regulating nitrogen content and heat treatment conditions.
[0039] 2. The method adopted by the present invention weakens the high-temperature serration amplitude of 316Mo injection-molded super austenitic stainless steel and improves the high-temperature mechanical properties, thereby narrowing the temperature range in which DSA occurs.
[0040] 3. The present invention can manufacture high-temperature parts with complex shape features, and the process is simple, which has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The illustrations are used to briefly describe the drawings in the specification. They are important technical means for recording technical solutions such as mechanical structures. They explain the legal basis and feasibility of the application of the illustrations in patent searches. At the same time, they provide application examples of the illustrations in patent searches, so that patent searches can effectively improve search efficiency compared to conventional search methods.
[0042] Figure 1 These are microstructure morphologies of 316Mo injection molded super austenitic stainless steel after solution treatment in Example 1 (a), Example 2 (b), and Example 3 (c) of the present invention.
[0043] Figure 2 The present invention discloses a nitrogen-free 316Mo super austenitic stainless steel (a). After modification, the present invention obtains different nitrogen contents of 0.179% N (b), 0.266% N (c), 0.296% N (d) and the sawtooth type (e) appearing on the stress-strain curves of the four materials after high-temperature uniaxial tensile deformation.
[0044] Figure 3These are SEM scanning images of the fracture surfaces of the uniaxially stretched samples of the comparative example (a), embodiment 1 (b), embodiment 2 (c), and embodiment 3 (d) of the present invention at 350°C.
[0045] Figure 4 These are pictures of the tensile test pieces of 316Mo super austenitic stainless steel after fracture of Comparative Example (a), Example 1 (b), Example 2 (c), and Example 3 (d) of the present invention. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with the embodiments.
[0047] Example 1
[0048] 1. Sample Preparation
[0049] 316Mo injection molded super austenitic stainless steel, the preparation process is raw material preparation - injection molding - vacuum sintering nitriding - heat treatment process. The details are as follows:
[0050] (1) Raw material preparation:
[0051] The invention discloses an injection-molded super austenitic stainless steel with reduced dynamic strain aging characteristics. Molybdenum is added to the traditional 316L stainless steel. The specific components include 20.51% Cr, 15.04% Ni, 6.08% Mo, 0.01% C, 0.11% O, 0.23% Mn, 0.21% Si, and the balance is Fe.
[0052] The injection molding super austenitic stainless steel powder is prepared by gas atomization, and the gas atomization pressure is 2-8 MPa of nitrogen. After the preparation, the powder particle size is D 10 =3-12μm, D 50 =9-18μm, D 90 =15-30μm, the powder particle size distribution is relatively concentrated, and under the combined effect of the atomizing medium nitrogen and the alloy elements at high temperature, a certain amount of nitrogen is dissolved in the powder, and the powder nitrogen content is about 0.01-0.02% N. The powder composition is as follows: 20.51% Cr, 15.04% Ni, 6.08% Mo, 0.01% C, 0.11% O, 0.23% Mn, 0.21% Si, and the balance is Fe.
[0053] (2) Injection molding:
[0054] Feed material preparation: The feed material preparation uses 10% by mass of a composite polyoxymethylene-based adhesive adapted to 316Mo heat-resistant austenitic stainless steel powder and 90% by mass of a metal raw material powder, and the mixing temperature on the mixer is 180°C, the mixing time is 1.5h, and the mixing speed is 30r / min;
[0055] The binder composition is polyoxymethylene (POM) 87.5wt.%, polyethylene (PE) 5wt.%, ethylene-vinyl acetate copolymer (EVA) 2wt.%, paraffin (PW) 2wt.%, stearic acid (SA) 2wt.%, antioxidant (B215) 1.5wt.%;
[0056] Injection molding: During injection, the mold temperature is 100℃, the nozzle temperature is 180℃, the first-stage injection temperature is 185℃, the second-stage injection temperature is 180℃, the third-stage injection temperature is 175℃, and the injection pressure is 90MPa.
[0057] Catalytic degreasing: carried out in a fuming nitric acid atmosphere, the catalytic degreasing temperature is 120°C, and the catalytic degreasing time is 6 hours;
[0058] (3) Vacuum sintering nitriding: The debinded blank is subjected to a nitrogen partial pressure of 20 KPa to obtain a nitrogen-containing 316Mo sample with a nitrogen content of 0.179 wt% 316Mo + 0.179 N%, which includes four parts: negative pressure debinding, vacuum sintering, partial pressure sintering and forced cooling.
[0059] Negative pressure degreasing stage: heat up to 350℃ at a rate of 5℃ / min and keep warm for 30min, then heat up to 600℃ at a rate of 5℃ / min and keep warm for 30min. During the negative pressure degreasing stage, the gas pressure is controlled to 0 and the flow rate of the protective gas is 20L / min.
[0060] Vacuum firing stage: the temperature is raised to 1050°C at a rate of 5°C / min and kept at that temperature for 30 minutes. During the vacuum firing stage, the gas pressure is controlled to 0 and no protective gas is introduced;
[0061] Partial pressure sintering stage: the temperature is raised to 1300°C at a heating rate of 5°C / min and kept at this temperature for 120 minutes. During the partial pressure sintering stage, the partial pressure of the protective gas is controlled to be 20KPa, and the flow rate of the protective atmosphere is 20L / min;
[0062] Cooling stage: cool down to 850℃ at a rate of 5℃ / min, and then cool in the furnace.
[0063] (4) Heat treatment process: The nitrided samples were subjected to solution treatment at a temperature of 1100 °C and a holding time of 2 h. After the solution treatment, they were water cooled.
[0064] The nitrogen content of the sample after sintering and nitriding is 0.179wt.%, the oxygen content is 0.11wt.%, and the carbon content is 0.0265wt.%.
[0065] The density of stainless steel parts can exceed 7.95g / cm 3 , nitrogen content is 0.179.wt%. The alloy needs to be heat treated.
[0066] like Figure 1 As shown in (a), after solution treatment, the sample with 0.179% N has a large number of white irregular precipitates dispersed in the crystal and blocky precipitates precipitated along the grain boundaries. The size of the blocky precipitates is 20-30 μm, and the spacing is 20-50 μm.
[0067] 2. Mechanical properties test
[0068] Test method: high temperature uniaxial tensile test, test conditions: test temperature is 350℃, 450℃, 550℃, 650℃, 750℃, test strain rate is 1.8×10 -3 s -1 , the mechanical testing machine is Instron3369.
[0069] Under this condition, the high temperature tensile test was carried out, and the results showed:
[0070] like Figure 2 (b) shows that under high temperature tensile conditions, at 350-450℃, the nucleation and propagation of the local deformation band of 0.179wt.%N 316Mo super austenitic stainless steel are suppressed, and no sawtooth fluctuation appears on the stress-strain curve; E-type sawtooth waves appear under high strain, producing slight fluctuations; at 650℃, 316Mo+0.179N% stainless steel begins to show A+B-type sawtooth fluctuations with a large amplitude at a strain value of 2.545%; at 750℃, the sawtooth amplitude The tensile strength decreases significantly with increasing temperature, and the yield strength decreases significantly from 578.76MPa to 353.06MPa. The yield strength decreases with increasing temperature, that is, the strengthening effect of dynamic strain aging is weaker than the softening effect caused by increasing temperature. The elongation after fracture first increases and then decreases. The high-temperature mechanical properties of the super austenitic stainless steel are improved. Therefore, the tensile strength at 750℃ is 350-355MPa, the yield strength is 180-185MPa, and the elongation after fracture is 20-21%.
[0071] Example 2
[0072] 1. Sample Preparation
[0073] The only difference from Example 1 is that the gas pressure is maintained at 50 KPa during the entire partial pressure sintering stage.
[0074] The nitrogen content of the sample obtained after sintering and nitriding was 0.266wt.%, the oxygen content was 0.082wt.%, and the carbon content was 0.026wt.%.
[0075] The density of stainless steel parts can exceed 7.95g / cm 3 , nitrogen content is 0.266.wt%. The alloy needs to be heat treated.
[0076] After solution treatment, the sample with 0.266% N has a moderate amount of white irregular precipitates dispersed in the crystal and blocky precipitates precipitated along the grain boundary. The size of the blocky precipitates is 20-25μm and the spacing is 30-50μm.
[0077] 2. Mechanical properties test
[0078] The high temperature tensile test was carried out under the same conditions as in Example 1, and the results showed that:
[0079] like Figure 2 As shown in (c), under high temperature tensile conditions, at 350-550°C, the nucleation and propagation of the local deformation band of 0.266wt.%N 316Mo super austenitic stainless steel are suppressed, and no sawtooth fluctuation appears on the stress-strain curve; at 650°C, 316Mo+0.266N% stainless steel begins to show A+B type sawtooth fluctuation with a large amplitude at a strain value of 2.694%, and the critical strain value for sawtooth yielding increases compared with Example 1; at 750°C, the sawtooth amplitude is significantly reduced, the tensile strength is 450-455MPa, the yield strength is 235-240MPa, and the elongation after fracture is 24-25%.
[0080] As the temperature increases, the tensile strength decreases significantly from 610.383MPa to 453.06MPa, and the yield strength decreases with the increase of temperature at 350-650℃, and increases with the increase of temperature at 650-750℃; the elongation after fracture first increases with the increase of temperature at 350-550℃, and decreases with the increase of temperature at 550-750℃. The high-temperature mechanical properties of this super austenitic stainless steel are improved.
[0081] Example 3
[0082] 1. Sample Preparation
[0083] The only difference from Example 1 is that the gas pressure is maintained at 80 KPa during the entire partial pressure sintering stage.
[0084] The nitrogen content of the sample after sintering and nitriding is 0.296wt.%, the oxygen content is 0.092wt.%, and the carbon content is 0.0217wt.%.
[0085] The density of the stainless steel parts can exceed 7.95g / cm3, and the nitrogen content is 0.296.wt%. The alloy needs to be heat treated.
[0086] like Figure 2(d) The sample with 0.296% N has a small amount of white irregular precipitates dispersed in the crystal and blocky precipitates precipitated along the grain boundaries after solution treatment. The size of the blocky precipitates is 20-25 μm and the spacing is 40-50 μm.
[0087] With the increase of nitrogen sintering pressure, the nitrogen content increases, the content of blocky substances decreases significantly, and the formation of intermetallic compounds is reduced.
[0088] 2. Mechanical properties test
[0089] The high temperature tensile test was carried out under the same conditions as in Example 1, and the results showed that:
[0090] Under high temperature tensile conditions, at 350-550℃, the nucleation and propagation of local deformation bands of 0.296wt.%N 316Mo super austenitic stainless steel are suppressed, and the stress-strain curve is smooth or slightly serrated. At 650℃, 316Mo+0.296N% stainless steel begins to show A+B type serrated fluctuations with a large amplitude at a strain value of 3.919%, and the critical strain value for serrated yielding increases compared with Example 1 and Example 2; at 750℃, the serrated amplitude is significantly reduced, the tensile strength is 415-420MPa, the yield strength is 270-273MPa, and the elongation after fracture is 25-27%.
[0091] As the temperature increases, the tensile strength decreases significantly from 669.465MPa to 416.789MPa, and the yield strength decreases with the increase of temperature at 350-550℃, and increases with the increase of temperature at 550-750℃; the elongation after fracture first increases with the increase of temperature at 350-550℃, and decreases with the increase of temperature at 550-750℃. The high-temperature mechanical properties of this super austenitic stainless steel are improved.
[0092] Comparative Example
[0093] 1. Sample Preparation
[0094] The difference from Example 1 is that the gas pressure is maintained at 15 KPa during the entire partial pressure sintering stage and the sintering atmosphere is argon. Since there is no nitriding during the sintering process, the obtained product has almost no nitrogen residue and the nitrogen content is 0.012%.
[0095] 2. Mechanical properties test
[0096] The high temperature tensile test was carried out under the same conditions as in Example 1, and the results showed that:
[0097] like Figure 2As shown in (a), under the condition of high temperature stretching, at 350℃, the nucleation and propagation of the local deformation band of the nitrogen-free 316Mo super austenitic stainless steel are suppressed, and no sawtooth fluctuation appears on the stress-strain curve; the initial temperature of the serration of 316Mo+0N% stainless steel is 450℃, and the sawtooth waveform that appears is type E. This type of sawtooth wave generally appears under high strain conditions. At 550℃, it mainly manifests as type A+B composite sawtooth. As the temperature increases, the distribution of type A+B sawtooth appears at 650℃ becomes more dense, and as the strain increases, it ends with type C sawtooth wave.
[0098] As the deformation temperature increases, the tensile strength of the material decreases from 524.355MPa to 287.337MPa, showing an overall downward trend; the yield strength of the material changes with temperature and dynamic strain aging occurs at 450°C, and the peak value appears with the appearance of dynamic strain aging. The elongation after fracture decreases, and the tensile strength of the comparative example is 285-288MPa, the yield strength is 155-160MPa, and the elongation after fracture is 12-13%.
[0099] Conclusion 1: From the sample preparation results, it is known that by adjusting the different parameters of the embodiment, the content of blocky matter is significantly reduced, resulting in a certain degree of fine grain strengthening, which has a certain influence on the density, strength and toughness of the prepared 316Mo austenitic stainless steel, so that the embodiment has high strength and better high temperature performance than the comparative example.
[0100] Conclusion 2: From the mechanical properties test results of Example 1, Example 2, Example 3 and the comparative example, it can be seen that nitrogen inhibits the DSA of 316Mo in the high temperature zone. The addition of nitrogen increases the critical strain for the appearance of high-temperature serrations and, at the same time, changes the characteristics of the appearance of serrations. The amplitude of the serrations in the embodiment is smaller than that in the comparative example.
[0101] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable technicians familiar with the technical field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A super austenitic stainless steel with reduced dynamic strain aging characteristics, characterized in that: The super austenitic stainless steel has the following composition by mass percentage: Cr 20-23%, Ni 14-16%, Mo 4.4-6.8%, C 0.01-0.2%, N 0.179-0.296%, O≤0.10%, Mn≤1%, Si≤1%, and the balance is Fe and unavoidable impurities.
2. The super austenitic stainless steel with reduced dynamic strain aging characteristics according to claim 1, characterized in that: The super austenitic stainless steel has the following composition by mass percentage: Cr 20-23%, Ni 14-16%, Mo 4.4-6.8%, C 0.01-0.2%, N 0.266-0.296%, O≤0.10%, Mn≤1%, Si≤1%, and the balance is Fe and unavoidable impurities.
3. The method for preparing a super austenitic stainless steel with reduced dynamic strain aging characteristics according to claim 1 or 2, characterized in that: The super austenitic stainless steel powder is mixed with a binder to obtain a feed material, the feed material is injection molded to obtain a rough blank, the rough blank is catalytically degreased to obtain a degreased blank, the degreased blank is nitrided and sintered to obtain a sintered blank, and the sintered blank is heat treated to obtain the super austenitic stainless steel.
4. The method for preparing super austenitic stainless steel with reduced dynamic strain aging characteristics according to claim 3, characterized in that: The super austenitic stainless steel powder is prepared by a gas atomization method, the gas atomization pressure is 2-8 MPa, and the gas atomization medium is nitrogen.
5. The method for preparing super austenitic stainless steel with reduced dynamic strain aging characteristics according to claim 3, characterized in that: The particle size of the super austenitic stainless steel powder is D 10 =3-12μm, D 50 =9-18μm, D 90 =15-30μm; In the super austenitic stainless steel powder, the mass fraction of N is 0.01-0.02%.
6. The method for preparing super austenitic stainless steel with reduced dynamic strain aging characteristics according to claim 3, characterized in that: In the feed, the mass fraction of the binder is 10-11%; The binder is a composite polyoxymethylene-based adhesive; The mixing temperature is 170-180°C, the mixing time is 1.5-2h, and the mixing speed is 30-35r / min; During the injection molding, the temperature of the mold is 90-100° C., the maximum injection temperature is 175-185° C., and the injection pressure is 80-90 MPa.
7. The method for preparing super austenitic stainless steel with reduced dynamic strain aging characteristics according to claim 3, characterized in that: The catalytic degreasing is carried out in a fuming nitric acid atmosphere, the temperature of the catalytic degreasing is 110-120° C., and the time of the catalytic degreasing is 4-6 hours.
8. The method for preparing super austenitic stainless steel with reduced dynamic strain aging characteristics according to claim 3, characterized in that: The temperature of the nitriding sintering is 1290-1340° C., the holding time is 1-4 hours, and the partial pressure of nitrogen is 20Kpa-80Kpa.
9. The method for preparing super austenitic stainless steel with reduced dynamic strain aging characteristics according to claim 8, characterized in that: The nitriding sintering process is composed of a negative pressure degreasing stage, a vacuum sintering stage, a partial pressure sintering stage, and a forced cooling stage. The process of the negative pressure degreasing stage is: firstly, the temperature is increased to 350-400°C at a heating rate of 3-5°C / min and kept for 30-120min, then the temperature is increased to 600-650°C at a heating rate of 3-5°C / min and kept for 30-240min. During the negative pressure degreasing stage, the gas pressure is controlled to be 0.001-0.1Pa, and the flow rate of the protective gas is 20-30L / min; the process of the vacuum sintering stage is: the temperature is increased to 1000-1100°C at a heating rate of 3-5°C / min. ℃ and keep warm for 30-90min. During the vacuum firing stage, the gas pressure is controlled to be 0.001-0.1Pa, and no protective gas is introduced. The process of the partial pressure sintering stage is: heating to 1290-1340℃ at a heating rate of 3-5℃ / min, keeping warm for 120-240min. During the partial pressure sintering stage, the partial pressure of the protective gas is controlled to be 20-80KPa, and the flow rate of the protective gas introduced is 20-30L / min. The process of the cooling stage is: cooling to 800-850℃ at a cooling rate of 5-15℃ / min, and then cooling with the furnace. The protective gas introduced in the partial pressure sintering stage is nitrogen.
10. The method for preparing super austenitic stainless steel with reduced dynamic strain aging characteristics according to claim 3, characterized in that: The heat treatment is a solution treatment, the temperature of the solution treatment is 1100° C.-1150° C., the time of the solution treatment is 2-4 hours, and water cooling is performed after the solution treatment is completed.
Citation Information
Patent Citations
Preparation method of high-nitrogen austenitic stainless steel
CN118756056A